COMPARATIVE ANALYSIS OF UZBEK AND ENGLISH SENTENCE STRUCTURES IN ACADEMIC WRITING - Aralova Madina Baxtiyor qizi (Bright Mind Publishing, 2025)
This article deals with Uzbek and English sentence structure differences in academic writing. The paper compares syntactic features of the two languages and explains how these differences are manifested in Uzbek students' English essays. Drawing on a qualitative analysis of 30 academic essays and 5 authentic Uzbek texts, the paper reveals main problems such as word order interference, lack of articles, and misuse of passive voice. The findings show that explicit contrastive grammar instruction can improve students' writing.
Keywords: Uzbek language, English language, sentence structure, academic writing, contrastive grammar, passive voice, article usage, linguistic transfer.